2020
DOI: 10.3390/w12061763
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Pouring Aggregate to Plug Horizontal Tunnel with Flow Water

Abstract: This paper presents an experimental investigation on the main factors that influence the effects of pouring aggregate to plug a tunnel that has been inundated by groundwater to reduce the flow velocity. Moreover, a criterion for plugging the tunnel under infiltrating water to resist flow is proposed. A range analysis and analysis of variance both show that the influencing factors on the efficiency of plugging in descending order is the aggregate particle size, followed by initial velocity of the water flow, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…This situation indicates that the plugging of water with pouring aggregate is successful. The efficiency of plugging and the main effects of pouring aggregate in a flowing tunnel have been discussed in the literature [11]. Figure 2 shows the pouring and accumulation process in Trial No.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation indicates that the plugging of water with pouring aggregate is successful. The efficiency of plugging and the main effects of pouring aggregate in a flowing tunnel have been discussed in the literature [11]. Figure 2 shows the pouring and accumulation process in Trial No.…”
Section: Resultsmentioning
confidence: 99%
“…A geometric ratio of 20 between the prototype and the model was selected based on the Euler criterion and the gravity similarity criterion. Based on previous research and similarity criteria, the pipeline can be used to simulate a tunnel with a cross-sectional area of 12 m 2 , length of 80 m and water-inrush flow of 6440 m 3 /h [11].…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that the aggregate pouring speed and particle size should be continuously adjusted to further reduce the seepage speed and create favorable conditions for grouting after successful capping. At this time, the water head difference between the two sides should be increased so that the slurry can propagate along the aggregate accumulation mass and improve the blocking effect (Zhang et al 2020). Integrated technology, differences and difficulties of bulkhead construction involving aggregate pouring and grouting in a tunnel under flowing water conditions were examined via a comparison to the general pregrouting method.…”
Section: Introductionmentioning
confidence: 99%
“…Using the Bingham model, they controlled the grouting and water flow rates and studied the antiscouring ability of the paste. Zhang et al [14] experimentally investigated porous aggregate infusions in a mine submerged beneath a roadway. By combining the results of an indoor experiment with theory, they established a visual pipelineaggregate infusion test platform for analyzing the hydrodynamic velocity and the influence of different factors on aggregate plugging.…”
Section: Introductionmentioning
confidence: 99%
“…Aggregate interception and water shutoff were mainly affected by the hydrodynamic velocity and aggregate particle sizes. From these results, Zhang et al [14] derived the law of aggregate sedimentary migration and accumulation. Li et al [15] developed a grouting-model test bed that visualizes fracture developments under a dynamic water supply.…”
Section: Introductionmentioning
confidence: 99%